The Ottoman Ibadis of Cairo: A History - Love Jr, Paul M. (Cambridge University Press, 2023)
Paul M. Love, Jr. explores the history of the minority Ibadi Muslim community in Cairo from the seventeenth to the early twentieth centuries. Using a unique range of sources, Love both illuminates the events of Egyptian history and highlights the role of the Ibadis in shaping political, religious, and commercial life in Ottoman-era Cairo.
Keywords: Emigration – Djebel Nefousa – Egypte; Emigration – Djerba – Egypte; Emigration – Mzab – Le Caire

الوقف الثقافي الإباضي والمالكي في مصر دراسة مقارنة - مصلح, أحمد بن مهني (اباديكا, 2024)
Keywords: Bibliothèques – Le Caire; Emigration – Djebel Nefousa – Egypte; Emigration – Djerba – Egypte; Emigration – Mzab – Le Caire; Manuscrits – Le Caire

البعثات العلمية لمعهد الحياة إلى المشرق العربي (الحلقة الثانية: بعثة القاهرة) - حمدي, محمد بن صالح (الحياة, 2018)
Keywords: Emigration – Mzab – Le Caire